PERKEMBANGAN PEMAHAMAN HADIS DI INDONESIA: Analisis Pergeseran Dan Tawaran Di Masa Kini - Taufan Anggoro (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
Some arguments assume that the study of hadith in Indonesia is rare. This argument that was indeed ‘rushed’ was refuted in this study by showing that the development of hadith studies in Indonesia showed a dynamic trend since the late 17th century until now. Through the analysis of this research shows how the development of hadith understanding in Indonesia in each period and its shift. In addition, trying to offer principles in understanding hadith in the present. As a result, the shift that arises there are four models: first, understanding the hadith in a simple way; second, understanding hadith is limited to internal hadith texts; third, to understand hadith contextually; and fourth, understanding textual-literal hadith. And some offers that can be used in understanding the hadith are four principles, namely the principle of equality, justice, non-radicalism, and non-politics.